2012
DOI: 10.1002/ijc.27598
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock gene BMAL1 is a novel therapeutic target for malignant pleural mesothelioma

Abstract: Malignant pleural mesothelioma (MPM) is a highly aggressive neoplasm arising from the mesothelial cells lining the parietal pleura and it exhibits poor prognosis. Although there has been significant progress in MPM treatment, development of more efficient therapeutic approaches is needed. BMAL1 is a core component of the circadian clock machinery and its constitutive overexpression in MPM has been reported. Here, we demonstrate that BMAL1 may serve as a molecular target for MPM. The majority of MPM cell lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 30 publications
(58 reference statements)
6
59
0
2
Order By: Relevance
“…Our findings are consistent with those of multiple studies demonstrating the role of Bmal1 in the suppression of cell proliferation, indicating that Bmal1 is a potential tumor suppressor gene (13)(14)(15). In contrast to our findings, another recent study (46) reported that Bmal1 promotes proliferation in malignant pleural mesothelioma. On the basis of this difference, we suspect that Bmal1 might play different roles in different tumor types, which further highlights the complicated mechanisms involved in tumorigenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with those of multiple studies demonstrating the role of Bmal1 in the suppression of cell proliferation, indicating that Bmal1 is a potential tumor suppressor gene (13)(14)(15). In contrast to our findings, another recent study (46) reported that Bmal1 promotes proliferation in malignant pleural mesothelioma. On the basis of this difference, we suspect that Bmal1 might play different roles in different tumor types, which further highlights the complicated mechanisms involved in tumorigenesis.…”
Section: Discussionsupporting
confidence: 93%
“…Because KS15 can enhance the actions of CLOCK:BMAL1, it is likely that the reduction in the Bmal1 level does not interfere with the anti-tumor activity of KS15. On the other hand, a recent study showed that repression of BMAL1 induces apoptosis and cell-cycle disruption in mesothelioma cells [41], suggesting the possibility of a novel contribution of Bmal1 reduction to the anti-tumor activity of KS15.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The median survival of 1 yr after diagnosis and the poor quality of life involved have prompted researchers to identify effective therapies with variable clinical results so far (48,73). MPM poses a diagnostic challenge, since its detection in early stages is often proven to be problematic, thus urging the importance of biomarker development (15,71).…”
mentioning
confidence: 99%